Receipt of Breast Milk by Gestational Age – United States, 2017 (P11-060-19). (13th June 2019) - Chiang, Katelyn; Sharma, Andrea; Nelson, Jennifer; Olson, Christine; Perrine, Cria
Abstract: Objectives: Breast milk is the optimal source of infant nutrition. For the nearly 1 in 10 infants born prematurely in the United States annually, breast milk is especially beneficial, helping prevent sepsis and necrotizing enterocolitis (NEC) and promoting neurological development. Though the importance of breast milk for preterm infants has been established, national estimates of feeding practices by gestational age are unavailable. Our objective was to describe receipt of breast milk among preterm and term infants delivered in the United States in 2017. Methods: Birth certificate data from 48 states and the District of Columbia (n = 3, 194, 873; 82.7% of all births) were analyzed to describe receipt of breast milk before birth certificate completion among extremely preterm (20-27 weeks), early preterm (28-33 weeks), late preterm (34-36 weeks) and term infants (≥ 37 weeks) with further stratification by maternal and infant characteristics. Results: The prevalence of infants receiving breast milk was 83.9% overall and varied by gestational age: 71.3% (extremely preterm), 76.0% (early preterm), 77.3% (late preterm), and 84.6% (term). Disparities in receipt of breast milk by maternal race/ethnicity were noted across gestational ages. Infants delivered to black or American Indian/Alaska Native mothers were the least likely to have received breast milk while those delivered to white, Hispanic, and Asian mothers were more likely to have received breast milk. Differences in receipt of breast milk by other maternal sociodemographic factors also persisted similarly across gestational ages. Among late preterm and term infants, receipt of breast milk was lower for those admitted to the neonatal intensive care unit (NICU) than those not admitted to the NICU. Conclusions: Fewer preterm than term infants received breast milk in the first few days of life. Optimal hospital policies and practices that support breast milk feeding and ensure availability of donor milk for high-risk infants may help improve infant nutrition and reduce infant morbidity and mortality. Mothers of infants admitted to the NICU may need additional support given the challenges associated with having a medically fragile infant such as mother-infant separation and extended infant hospitalization. Funding Sources: Centers for Disease Control and Prevention, Oak Ridge Institute for Science and Education.